Polarimetry of the Eclipsing Pulsar PSR J1748-2446A - You, X.; Manchester, R.; Coles, W.; Hobbs, G.; Shannon, Ryan (Institute of Physics Publishing, 2018)
© 2018. The American Astronomical Society. All rights reserved.. Observations with the Parkes radio telescope of the eclipsing millisecond binary pulsar PSR J1748-2446A, which is in the globular cluster Terzan 5, are presented. These include the first observations of this pulsar in the 3 GHz frequency band, along with simultaneous observations in the 700 MHz band, and new observations around 1400 MHz. We show that the pulsar signal is not eclipsed in the 3 GHz band and observe the known eclipses in the lower-frequency bands. We find that the observed pulse signal becomes depolarized during particular orbital phases and postulate that this depolarization occurs because of rotation-measure fluctuations resulting from turbulence in the stellar wind responsible for the eclipses.